Producción científica del personal de Enfermería. Chimborazo 2019 - Cisneros Catucuago, Jessica Gabriela (2020)
Research is a permanent social process necessary to transform the professional profile; that is, it responds to the needs of the user, family, and community according to their contexts. Therefore, nursing staff must develop a research function in all work areas, allowing the improvement of their profession. The objective of this study is to describe the scientific production of the nursing staff of the Health District 06D05 Guano-Penipe2 in the province of Chimborazo during the period from May 2019 to April 2020, under a descriptive, observational study, this will work with the entire population that works in different health posts. Among the most relevant results are: the majority of professionals obtained their degree through a research project, but none have carried out postgraduate studies. The publication is limited, possibly due to the lack of dissemination of existing journals and the lack of training in scientific writing that guarantees release; however, there is interest in research due to its importance in professional practice. The Ministry of Health has organized permanent training that motivates them to carry out scientific research with some ease but requires financing that stimulates the research training process until publication in indexed journals and its application in daily practice. A proposed action plan with strategies will stimulate research.